Development of a respiratory system module for third year medical education in a problem-based learning curriculum - Pena-Sulay, Liza Stefanie (2006)
The Cebu Doctors' University - College of Medicine (CDU-CM) began its problem-based curriculum in 2003. Modules to guide the faculty were developed, including the Respiratory System Module, which is the subject of this study. Its development followed the research and development cycle. Research, planning and development of the module involved review of literature and documents on problem-based learning, the CDU-CM program, and the problems to be included in the module observation of small group discussions, and several focus group discussions and meetings with key personnel. Multiple-choice quizzes for the students and a questionnaire for both facilitators and students were also developed and accomplished at the end of the module. In developing the module, national bodies' goals, the college's objectives, learning philosophy and program, and resources, as well as the characteristics of the facilitators and learners were taken into account. The final module contained general and specific objectives and the schedule of activities that included four problems for the small group discussions, independent study time, correlate activities as lectures and laboratory sessions, and two quizzes. The problems were chosen for their emergent nature or their commonality and relevance in the national setting. These were pneumothorax and pleural effusion; pulmonary edema; chronic obstructive disease; and pulmonary masses. Each problem was further elaborated into a case scenario, list of tasks, concept map, detailed tutor guide, and list of references. A field test of the module was conducted on the whole population of third year medical students at the CDU-CM. Though they were able to formulate the correct diagnosis and concept map for each of the problems, the tasks were found to be long, disorganized and confusing. Lack of adequate time for study was a frequently encountered complaint. The tasks were revised accordingly, in preparation and use on the next batch of third year students. No one passed the two quizzes. Item analysis found 28% of the items in the first quiz, and 16% of the items in the second quiz lacking in validity and reliability. However, students were also found to have difficulty integrating their knowledge and applying it to clinical scenarios. This shows that they may have failed to develop the basic cognitive structures necessary to understand, assimilate, and use new information. Some of the problems encountered with this module may reflect those encountered with PBL modules in the Philippines in general. First, the licensure examination is mainly disease-based, not problem-based. Second, the main textbooks are likewise disease-based. Third, although the PBL process of research, analysis and application is admirable, it is time-consuming for students who are pressured to finish their studies and pass the licensure examination after five years of study. It would seem that, at least in our setting, the goal of passing the examination still takes precedence over life-long learning.
Major project (Master in Health Professions Education)--University of the Philippines Manila
Keywords: Problem-based learning -- Curricula